Perceptions of users and providers on barriers to utilizing skilled birth care in mid- and far-western Nepal: a qualitative study - Onta, Sharad (Co-Action Publishing, 2014)
BACKGROUND: Although skilled birth care contributes significantly to the prevention of maternal and newborn morbidity and mortality, utilization of such care is poor in mid- and far-western Nepal. This study explored the perceptions of service users and providers regarding barriers to skilled birth care. DESIGN: We conducted 24 focus group discussions, 12 each with service users and service providers from different health institutions in mid- and far-western Nepal. All discussions examined the perceptions and experiences of service users and providers regarding barriers to skilled birth care and explored possible solutions to overcoming such barriers. RESULTS: Our results determined that major barriers to skilled birth care include inadequate knowledge of the importance of services offered by skilled birth attendants (SBAs), distance to health facilities, unavailability of transport services, and poor availability of SBAs. Other barriers included poor infrastructure, meager services, inadequate information about services/facilities, cultural practices and beliefs, and low prioritization of birth care. Moreover, the tradition of isolating women during and after childbirth decreased the likelihood that women would utilize delivery care services at health facilities. CONCLUSIONS: Service users and providers perceived inadequate availability and accessibility of skilled birth care in remote areas of Nepal, and overall utilization of these services was poor. Therefore, training and recruiting locally available health workers, helping community groups establish transport mechanisms, upgrading physical facilities and services at health institutions, and increasing community awareness of the importance of skilled birth care will help bridge these gaps.